Top Ten Resolutions for Utility Executives in 2022: Addressing Major Issues Impacting Utilities for the Coming Year and Decade Ahead. (8th January 2022) - Price, Jason; Shah, Niki
Abstract : When the clock strikes midnight on December 31st we embrace the new year with a fresh start. However, utilities do not have the luxury of starting the new year from a clean slate. As each year passes, the utility's role grows more complicated; arrearages are increasing year‐over‐year, the planet is getting warmer and weather events are more severe, calls for decarbonization are getting louder, and the world is demanding the energy industry take action. While utilities are not in the business of solving the world's problems, regulators, policy makers and the general public expects results.